2016
DOI: 10.5966/sctm.2016-0023
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Clinical Observation of Arthroscopic Microfracture in the Presence and Absence of a Stromal Vascular Fraction Injection for Osteoarthritis

Abstract: Osteoarthritis (OA) is a degenerative cartilage disease that is characterized by a local inflammatory reaction. Consequently, many studies have been performed to identify suitable prevention and treatment interventions. In recent years, both arthroscopic microfracture (AM) and stem cell therapy have been used clinically to treat OA. This study aimed to evaluate the clinical effects of AM in the presence and absence of a stromal vascular fraction (SVF) injection in the management of patients with OA. Thirty pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
169
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(174 citation statements)
references
References 81 publications
5
169
0
Order By: Relevance
“…Adipose tissues from patients were collected according to a previously published study (Nguyen et al, 2016). Briefly, patients were given local anesthesia with 2-3 mL of marcaine (5 g/L); the lower abdomen area was also anesthetized.…”
Section: Adipose Tissue Aspirationmentioning
confidence: 99%
“…Adipose tissues from patients were collected according to a previously published study (Nguyen et al, 2016). Briefly, patients were given local anesthesia with 2-3 mL of marcaine (5 g/L); the lower abdomen area was also anesthetized.…”
Section: Adipose Tissue Aspirationmentioning
confidence: 99%
“…Patients have experienced improvements in pain, function, mobility, and overall quality of life on various clinical questionnaires after SVF and ASC administration into the affected joints (Fig. H) . Clinical improvement persisted in these studies for several months to more than two years.…”
Section: Resultsmentioning
confidence: 80%
“…Various studies have been conducted in which human patients with osteoarthritis of the knee received an intra‐articular injection with autologous SVF and ASC. Many of the studies specifically recruited patients with osteoarthritis which was refractory to oral medications, physical therapy, autologous cartilage transplantation, and hyaluronic acid injection . Patients have experienced improvements in pain, function, mobility, and overall quality of life on various clinical questionnaires after SVF and ASC administration into the affected joints (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some recent studies have shown that autologous adipose stem cell transplantation can improve osteoarthritis (Bui et al, 2014). Combination of stem cell transplantation and microfracture have also proven to be better than microfracture alone (Nguyen et al, 2016). However, similar to osteochondral allograft transplantation and autologous chondrocyte implantation, stem cell transplantation is expensive but yields promising results in clinical trials.…”
Section: Introductionmentioning
confidence: 99%